Associations of Anthropometric Characteristics, Dietary Habits, and Aerobic Capacity With Cardiovascular Risk Factors of Health-Science Students. Issue 5 (October 2018) - Zarrazquin Arizaga, Idoia; Atucha, Ainhoa Fernández; Kortajarena, Maider; Torres-Unda, Jon; Irazusta, Amaia; Ruiz-Litago, Fátima; Irazusta, Jon; Casis, Luis; Fraile-Bermúdez, Ana Belen
The aim of this cross-sectional study was to study the relative importance of dietary habits and aerobic capacity in parameters related to cardiovascular risk in 271 female and 95 male health-science students (mean age = 19.1 ± 1.4 years). In females, fatty-meat consumption predicted triglycerides (β = .649, p < .001) and high-density lipoprotein (HDL; β = −.242, p = .001) and low-density lipoprotein (LDL; β = .373, p < .001) cholesterol levels. Consumption of nuts, legumes, and complex carbohydrates predicted triglyceride (β = −.099, p = .074), HDL (β = .231, p = .001), and LDL (β = −.155, p = .025) levels, respectively. Aerobic capacity (β = −.245, p < .001) and fatty-meat intake (β = .230, p < .001) predicted diastolic blood pressure (BP); body mass index (BMI) predicted systolic BP (β = .340, p < .001). In males, body fat percentage was the strongest predictor of triglycerides (β = .348, p = .004), cholesterol (β = .366, p = .006), HDL (β = −.378, p = .004), and LDL (β = .271, p = .043) levels. Aerobic capacity (β = −.263, p = .013) and fatty-meat consumption (β = .334, p = .005) independently predicted triglyceride levels. Nut (β = −.286, p = .013) and fatty-meat intake (β = .361, p = .002) predicted systolic BP, while BMI predicted diastolic BP (β = .209, p = .045). As health sciences students, these participants are future health professionals; targeting such populations is important for chronic disease prevention.